HAK PEKERJA PASCA PERUSAHAAN DIAKUISISI - CHRISTINA NM TOBING (LP2MTBM MAKARIOZ, 2023)
The purpose of this research is to find out the rights of workers due to the company being acquired by another company according to the Labor Law before and after the Job Creation Law. This research is normative legal research, the data sources used are secondary data in the form of legislation, expert opinions, and research results. The research approach used is the statutory approach. Data analysis was carried out qualitatively. The results of the research, before and after the Job Creation Law, workers' rights in the event that a company is acquired by another company according to the Labor Law, in principle, has given equal rights to employers, where each party can choose not to continue the employment relationship (PHK) or vice versa, continue the employment relationship. Nonetheless, the decision to lay off or no longer be given to employers is implied in the words of Article 163 paragraphs (1) and (2) of the Manpower Law jo. Article 42 paragraph (1) PP No. 35 of 2021 with the words